Effect of cariporide on ram sperm pH regulation and motility: possible role of NHE1. Issue 5 (May 2018) - Muzzachi, Stefania; Guerra, Lorenzo; Martino, Nicola Antonio; Favia, Maria; Punzi, Giuseppe; Silvestre, Fabio; Guaricci, Antonio Ciro; Roscino, Maria Teresa; Pierri, Ciro Leonardo; Dell'Aquila, Maria Elena; Casavola, Valeria; Lacalandra, Giovanni Michele; et al.
Abstract : Sperm motility, a feature essential for in vivo fertilization, is influenced by intracellular pH (pHi ) homeostasis. Several mechanisms are involved in pHi regulation, among which sodium–hydrogen exchangers (NHEs), a family of integral transmembrane proteins that catalyze the exchange of Na + for H + across lipid bilayers. A preliminary characterization of NHE activity and kinetic parameters, followed by analysis of the expression and localization of the protein in ram spermatozoa was performed. NHE activity showed an apparent K m for external Na + of 17.61 mM. Immunoblotting revealed a molecular mass of 85 kDa. Immunolocalization pattern showed some species-specific aspects, such as positive labeling at the equatorial region of the sperm head. Cariporide, a selective NHE1 inhibitor, significantly reduced pHi recovery (85%). Similarly, exposure to cariporide significantly inhibited different motility parameters, including those related to sperm capacitation. In vitro fertilization (IVF) was not affected by cariporide, possibly due to the non-dramatic, although significant, drop in motility and velocity parameters or due to prolonged exposure during IVF, which may have caused progressive loss of its inhibitory effect. In conclusion, this is the first study documenting, in a large animal model (sheep) of well-known translational relevance, a direct functional role of NHE on sperm pHi and motility. The postulated specificity of cariporide toward isoform 1 of the Na + /H + exchanger seems to suggest that NHE1 may contribute to the observed effects on sperm cell functionality.